Studi Analisis-Teologis Pembenaran oleh Iman dalam Surat Roma - Warseto Freddy Sihombing; Marlinawati Situmorang (Jurnal Teologi Cultivation, 2021)
Abstract:    Based on the analysis-theology of Romans, no man can be justified before God because he has done a good deed. No matter how good a man is, if he does not believe in Jesus Christ, the Son of God, he will not be saved from wrath of God to come The purpose of this article is to give the correct meaning of men justification before God through faith in the work of Jesus Christ. Based on the theological studies in Romans, Paul's teaching about justification by faith is a doctrine has enormous implications in Christians’ live: to be righteous because of Jesus Christ, to have the peace of God and to have access to fellowship with God. Keywords: faith, justified; Romans Abstrak:Berdasarkan analisis-teologis terhadap surat Roma, tidak ada seorang pun yang dapat dibenarkan di hadapan Allah karena telah melakukan perbuatan baik. Sebaik apa pun manusia, jika dia tidak percaya kepada Yesus Kristus, Anak Allah, maka, ia tidak akan selamat dari murka Allah yang akan datang. Tujuan artikel ini memberikan makna yang benar tentang pembenaran manusia di hadapan Allah melalui iman kepada karya Yesus Kristus. Berdasarkan kajian teologis dalam Surat Roma, ajaran Paulus mengenai pembenaran oleh iman adalah doktrin yang berimplikasi sangat besar dalam kehidupan orang Kristen: menjadi benar karena Yesus Kristus, memiliki damai sejahtera Allah dan beroleh akses untuk bersekutu dengan Allah. Kata kunci: iman; pembenaran; surat Roma.